Kajian Fiqh Jinayah Terhadap Hukuman Qishash dalam Kasus Pembunuhan - Limbong, Muhammad Fajar Miliano; Wahyudi, Muhammad Rolly; Sitorus, Muhammad Dzarril Ghofar; Fadila, Farhan; Hayati, Cut Rahma; Pulungan, Nondang; Siregar, Deliana (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study discusses the application of qishash punishment in murder cases according to fiqh jinayah, as well as its impact on the Islamic justice system and society. Qishash, which means proportionate retribution, is a form of punishment regulated in Islamic law for the perpetrator of intentional murder. As a legal concept rooted in the principle of justice, qishash aims to restore social balance and provide a deterrent effect for criminals. However, its application in society is not simple, as there are challenges related to unclear evidence, social and cultural considerations, and criticism of the application of the death penalty in the context of human rights. This study uses a qualitative method with a literature study approach to analyze various relevant fiqh and legal texts regarding qishash, as well as real cases that show its application in countries that apply Islamic law. The results of the study show that although qishash is considered a form of justice in Islamic law, its application is faced with problems such as injustice that can arise due to insufficient evidence, as well as controversies related to the death penalty. In addition, the role of the victim's family in choosing between qishash or diyat also shows that there are differences in views influenced by social, cultural, and economic factors. Considering the principles of justice in Islam and the challenges that arise in legal practice, this study concludes that the application of qishash in murder cases needs to be adapted to the times, including in terms of respecting human rights and upholding transparent and fair justice. This research also emphasizes the importance of developing an Islamic criminal law system that is able to accommodate human values without ignoring the principles of justice contained in fiqh jinayah.